2011
DOI: 10.1155/2011/949072
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Talk between Apolipoprotein E and Cytokines

Abstract: Apolipoprotein E (apoE) is a multifunctional glycosylated protein characterized by its wide tissue distribution. Despite its importance in lipid transport and atherosclerosis pathogenesis, apoE is associated with neurodegenerative disorders such as Alzheimer's disease (AD) and Parkinson disease, and autoimmune disorders such as multiple sclerosis and psoriasis. Among others, the role of apoE in modulating inflammation and oxidation is crucial in elucidating the risk factors of the above diseases since the func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
149
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(155 citation statements)
references
References 112 publications
5
149
0
1
Order By: Relevance
“…For instance, we and others have reported that the apoCI apolipoprotein may augment the general inflammatory state 41e44 . ApoE has also been implicated in systemic inflammatory processes, although it can exert both anti-and proinflammatory actions depending on the specific isoform 45,46 . Alternatively, the higher male susceptibility may also be explained by higher androgen levels, which exacerbate OA in mice 47 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, we and others have reported that the apoCI apolipoprotein may augment the general inflammatory state 41e44 . ApoE has also been implicated in systemic inflammatory processes, although it can exert both anti-and proinflammatory actions depending on the specific isoform 45,46 . Alternatively, the higher male susceptibility may also be explained by higher androgen levels, which exacerbate OA in mice 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Human studies also support a role of sex hormones in OA, showing increased OA prevalence and severity in postmenopausal women compared with premenopausal women and age-matched men 48,49 . Moreover, androgens and ApoE isoforms have been shown to be functionally intertwined in inflammatory processes 46,50 , providing a possible rationale as to why ApoE*3Leiden.CETP males show more cartilage degradation in response to metabolic challenges compared with females. Contrary to the males, female ApoE*3Leiden.CETP transgenic mice showed less cartilage degradation on chow but were susceptible to diet-induced OA.…”
Section: Discussionmentioning
confidence: 99%
“…Apo E, a glycoprotein, is expressed in numerous tissues within body [11]. Its different genotypes are related to the lipid concentration level and have already been implicated as association risk factors in cardiovascular disorders, strokes, Alzheimer disease and as susceptibly factor in response to viral, bacterial and parasitic infection [14]. Compared to E3, the most frequent allele, E4 allele of Apo E has a less affinity for LDL receptor which leads to decreased affinity for collection of chylomicrons from blood circulation [18].…”
Section: Discussionmentioning
confidence: 99%
“…For a successful pregnancy there should be equilibrium between inflammatory agents and anti-inflammatory cytokine factors [21]. Interleukin 10 (IL10) is the most potent amongst antiinflammatory factor [14]. It has been shown that in carriers of allele E4, IL10 plasma concentration is reduced [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation